Tantangan dan Solusi Pendidikan Keperawatan pada Masa Pandemi Covid 19 di Indonesia (Tinjauan Literatur) - Ade Suryaman; Ismail Fahmi; Amelia Ganefianty (Jurnal Penelitian Kesehatan SUARA FORIKES, 2021)
COVID-19 is still a pandemic health problem around the world. Many sectors have been affected by the COVID-19, including the nursing education sector. Social distancing policy by the government make nursing education administrators have to change learning methods. On the other hand, education administrators are required to be able to produce quality nurse graduates, even with online learning methods. This article is a literature review that aims to analyze the impact of COVID-19 on nursing education and solutions in dealing with it. We usd article search sources in the Pubmed database with the inclusion criteria for articles from 2020 to 2021 and provide full-text. The keywords used were "nursing education", "pandemic", "nursing challenge", and "college in a pandemic". The results showed that distance learning in the nursing education system can increase stress in students. Nursing education was required to innovate in carrying out learning activities, including making practical module videos, discussing and interacting with each subject, reducing practice hours, and transferring hospital practices to laboratory practices. Keywords: COVID-19; pandemic; nursing education; professional nurse ABSTRAK COVID-19 masih menjadi permasalahan kesehatan pandemi di seluruh dunia. Banyak sektor yang terdampak dari kondisi pandemi COVID-19, termasuk sektor pendidikan keperawatan. Pembatasan Sosial Berskala Besar (PSBB) oleh pemerintah menjadikan penyelengara pendidikan keperawatan harus merubah metode pembelajaran. Di sisi lain, penyelengara pendidikan ditutntut untuk dapat menghasilkan lulusan perawat yang berkwalitas, walaupun dengan metode pembelajaran online. Artikel ini merupakan suatu literature review yang bertujuan untuk menganlisis dampak COVID-19 terhadap pendidikan keperawatan dan solusi dalam menghadapinya. Kami menggunakan sumber pencarian artikel dalam database Pubmed dengan kriteria inklusi artikel tahun 2020 hingga 2021 dan menyediakan full-text. Kata kunci yang digunakan adalah “nursing education”, “pandemic”, “nursing challenge”, dan “college in pandemic”. Hasil penelusuran menunjukkan bahwa pembelajaran jarak jauh pada sistem pendidikan keperawatan dapat meningkatkan stres pada peserta didik. Sehingga dibutuhkan dukungan keluarga dan kebersamaan dengan keluarga agar dapat menurunkan tingkat stres peserta didik. Pendidikan keperawatan dituntut untuk berinovasi dalam melakukan kegiatan pembelajaran, meliputi pembuatan video modul praktek, diskusi dan interaksi pada setiap mata ajaran, pengurangan jam praktik, serta pengalihan praktik rumah sakit kepada praktik laboratorium. Kata kunci: COVID-19; pandemi; pendidikan keperawatan; perawat profesional